Suspensions for thermal spray coatings

JP2024515166A5Pending Publication Date: 2025-04-09TREIBACHER IND AG
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2023561618
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-04-07
Filing Date
2022-04-06
Publication Date
2025-04-09

AI Technical Summary

Technical Problem

Existing suspension thermal spraying methods often produce coatings with defects such as cylindrical structures and nodules, requiring additional equipment like air cross jets or water shrouds to achieve defect-free coatings, which increases cost and effort.

Method used

A suspension with a fine fraction ratio (FFR) of 0.5 or less, comprising solid ceramic particles with a particle size distribution between 2 μm and 10 μm, is used to produce dense coatings without the need for additional equipment, by controlling particle agglomeration and inertia in the spray jet.

Benefits of technology

The solution results in dense, crack-free, and smooth coatings with reduced thermal stress and improved deposition efficiency, suitable for corrosion-resistant, erosion-resistant, and scratch-resistant applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

The invention relates to a suspension for suspension thermal spraying, comprising solid ceramic particles and a solvent, characterized in that the suspension has a fine fraction ratio of less than or equal to 0.5, the fine fraction ratio being defined as the ratio between: - the volume fraction of solid ceramic particles having a particle size of less than or equal to 1.0 μm, as determined from a particle size distribution obtained from particle size analysis using laser diffraction particle analysis; and - the mass fraction of solid ceramic particles in the suspension, the density of the solid ceramic particles being 3.0-7.0 g / cm3, and the solid ceramic particles having a particle size distribution with a volume-based d50 value in the range of 2 μm to 10 μm.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to suspensions for suspension thermal spraying. [Background technology]

[0002] Suspension spraying, for example suspension plasma spraying, has become an emerging technology for producing coatings.

[0003] Suspensions as a feedstock for thermal spraying allow the use of fine particles, typically with an average size (d50) of less than 10 μm, and offer many advantages compared to conventional thermal spraying with solid feedstocks such as powders. Suspension spraying allows for lower surface roughness and coating porosity, and smaller pore sizes. Furthermore, suspension spraying with small particles is beneficial for pneumatic spray delivery systems.

[0004] Depending on the suspension properties (e.g., viscosity, surface tension, particle size, solids loading), suspension spraying produces columnar and dense coatings. In addition, coatings with thicknesses of several micrometers can be obtained using the suspension materials. Smooth and dense coatings are of particular interest for wear and corrosion resistant applications and electrical insulation.

[0005] The preferred suspension spraying method for producing dense coatings is suspension plasma spraying (SPS). In suspension plasma spraying, a suspension is introduced into a spray jet of hot, high velocity plasma gas and atomized into smaller droplets. The original solid particles then agglomerate as the liquid vaporizes, thereby increasing in size. These spray particles are melted by the hot plasma gas and accelerated towards the surface to be coated. Upon impacting the cold, solid surface, the spray particles are flattened into what are commonly called splats, which cool and solidify to form the sprayed coating.

[0006] The general principles of suspension plasma spraying of dense ceramic coatings are disclosed in US Pat. No. 5,609,921, US Pat. No. 6,579,573 and US Patent Publication No. 2006 / 0222777.

[0007] VanEvery et al. (Journal of Thermal Spray Technology, Vol. 20(4), No. 817-828 (2011)) discuss the effect of suspension droplet size and deposition grain size on coating microstructure. Small deposition particles with low inertia follow the gas jet close to the substrate and are deposited at an impact angle that is not perpendicular to the substrate surface, forming columnar structures (defects). In contrast, large deposition particles with high inertia maintain their trajectory and impact the coating surface at an angle close to 90°, forming a dense microstructure. Typically, starting from the same suspension droplet size, small deposition particles are formed when the suspension contains small solid particles at a low concentration, whereas large deposition particles are formed when the suspension contains large or small particles at a high concentration.

[0008] Further background on coating formation is disclosed in L. Pawlowski, Surface & Coatings Technology, Vol. 203(19), pp. 2807-2829 (2009). Curry et al. (Coatings, Vol. 5, pp. 338-356 (2015)) disclose that droplet size of a suspension is controlled by the properties of the suspension, in particular the viscosity, surface tension and density (solids loading) of the suspension. Further prior art is disclosed in Kitamura et al., Journal of Thermal Spray Technology, Vol. 20(1-2), pp. 170-185 (2011), U.S. Patent Application 2019 / 0242001 (A1), and Aghasibeig et al., Journal of Thermal Spray Technology, Vol. 28, pp. 1579-1605 (2019).

[0009] Commercially available suspensions are either ethanol-based for producing cylindrical coatings or water-based for producing dense coatings. Mixtures of ethanol and water have also been reported but are not widely used in the industry.

[0010] State-of-the-art suspensions for wear-resistant coatings typically contain about 25-40 wt.% chromia, alumina or titania in an aqueous liquid. For applications where a smooth and dense coating is required, these suspensions increase the formation of columnar defects (Kiilakoski et al., Journal of Thermal Spray Technology, Vol. 28, pp. 1933-1944 (2019)). These defects can be called "nodules."

[0011] Defect-free coatings can only be produced when additional equipment is used to remove fine particles from the spray jet, such as, for example, an air cross-jet (Kiilakoski et al., Journal of Thermal Spray Technology, Vol. 28, pp. 1933-1944 (2019)) or a water shroud (U.S. Pat. No. 10,279,365). Such additional equipment is undesirable due to the increased cost and labor involved.

[0012] Further prior art related to the technology of the present disclosure is disclosed in U.S. Patent Application Publication No. 2020 / 0048752; Forg et al., “Suspension and coating characterization of high velocity suspension flame sprayed (HVSFS) mixed titanium oxide-titanium carbide coatings,” Surf. Coatings Tech. Vol. 371, pp. 90-96 (2019); Arevalo et al., “An investigation of the dispersion of YSZ, SDC, and mixtures of YSZ / DSC powders in aqueous suspensions for application in suspension plasma spraying,” Surf. Coatings Tech. Vol. 205, pp. 5218-5227 (2011), and EP 3,778,981. Summary of the Invention

[0013] It is an object of the present invention to provide a suspension for suspension thermal spraying which overcomes the drawbacks of the state of the art and is capable of producing dense, defect-free coatings without the use of further technical measures such as air cross-jets or water shrouds.

[0014] This object is solved by a suspension comprising solid ceramic particles and a solvent, characterized in that the suspension has a fine fraction ratio (FFR) less than or equal to 0.5. According to the invention, the fine fraction ratio is the volume fraction of solid ceramic particles having a particle size of 1.0 μm or less, as determined from the particle size distribution; - mass fraction of solid ceramic particles in the suspension and It is defined as the ratio of The density of the solid ceramic particles is 3.0-7.0g / cm 3 and The solid ceramic particles are divided into d50 It has a particle size distribution with values ​​ranging from 2 μm to 10 μm.

[0015] Therefore, the present invention considers the different particle size distribution of particles in the suspension and the particle aggregation process in the spray jet during suspension spraying, and defines a critical ratio of fine content in the particle size distribution of the solid content of the suspension to the solid concentration in this suspension. The fine fraction ratio defines the minimum criterion for the suspension composition to form spray particles large enough to naturally produce a bump-free dense coating structure.

[0016] The present invention is particularly useful for producing corrosion-, erosion- and / or scratch-resistant coatings, especially those having a dense microstructure and a smooth surface.

[0017] The ability to reduce bumps is inherent to the suspension formulation. The low FFR reduces fine particle formation in the spray jet, thereby preventing columnar defect formation. No additional technical devices such as air cross jets or water shrouds are required to remove fine particles from the spray jet.

[0018] The suspension according to the invention with low FFR allows the spray distance to be reduced, because the larger spray particles in the spray jet have higher inertia. Increasing the spray distance reduces the thermal load on the coating and prevents cracks due to thermal stress. Furthermore, the deposition efficiency is automatically higher, since more material reaches the substrate when fine particles do not need to be removed from the spray jet by additional means. [Brief description of the drawings]

[0019] [Figure 1A]FIG. 1 shows an SEM BSE image of a polished cross-section of the coating obtained in Example 1 (magnification: 170x, accelerating voltage: 15.0 kV, working distance, WD: 10.2 mm), revealing a dense, crack- and defect-free microstructure and a smooth surface. [Figure 1B] SEM BSE images of the same cross section are shown consecutively (magnification: 170x, accelerating voltage: 15.0 kV, WD: 10.1 mm). [Diagram 2] FIG. 1 shows an SEM BSE image of a polished cross section of the coating obtained in Example 2 (magnification: 60x, accelerating voltage: 15.0 kV, WD: 10.1 mm), revealing a dense, crack- and defect-free microstructure and a smooth surface. [Diagram 3] FIG. 1 shows an SEM BSE image of a polished cross section of the coating obtained in Example 3 (magnification: 60x, accelerating voltage: 15.0 kV, WD: 11.8 mm), revealing a dense, crack- and defect-free microstructure and a smooth surface. [Figure 4A] FIG. 4A shows an SEM BSE image of a cross section of the coating obtained in Comparative Example 1A, depicting a bimodal coating structure with an uneven (rough) surface (FIG. 4A: magnification: 1000x, accelerating voltage: 15.0 kV, WD: 11.5 mm). [Figure 4B] FIG. 4B shows an SEM BSE image of a cross section of the coating obtained in Comparative Example 1A, depicting a bimodal coating structure with an uneven (rough) surface (FIG. 4B: magnification: 1000x, accelerating voltage: 15.0 kV, WD: 11.5 mm). [Figure 4C] FIG. 4C shows an SEM BSE image of a cross section of the coating obtained in Comparative Example 1A, depicting a bimodal coating structure with an uneven (rough) surface (FIG. 4C: magnification: 1000x, accelerating voltage: 15.0 kV, WD: 10.0 mm). [Figure 4D] FIG. 4D shows an SEM BSE image of a cross section of the coating obtained in Comparative Example 1A, depicting a bimodal coating structure with an uneven (rough) surface (FIG. 4D: magnification: 1000x, accelerating voltage: 15.0 kV, WD: 9.8 mm). [Diagram 5]An SEM BSE image of a polished cross-section of the resulting coating, prepared in the same manner as described in Example 1B, shows a generally flat surface with scattered / occasional surface irregularities in the form of bumps formed in a single column (magnification: 500x, accelerating voltage: 15.0 kV, WD: 10.2 mm). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0020] In a first aspect, the present invention provides a suspension for suspension thermal spraying, comprising solid ceramic particles and a solvent, the suspension having a fine fraction ratio of 0.5 or less, the fine fraction ratio being defined as the ratio between: - the volume fraction of solid ceramic particles having a particle size of 1.0 μm or less, as determined from the particle size distribution, and - the mass fraction of solid ceramic particles in the suspension, the density of the solid ceramic particles being 3.0 to 7.0 g / cm. 3 and the solid ceramic particles are d 50 It has a particle size distribution with values ​​ranging from 2 μm to 10 μm.

[0021] In a second aspect, the present invention provides the use of said suspension for suspension thermal spraying.

[0022] The following disclosure applies equally to the first and second aspects.

[0023] As used herein, the term "suspension spraying" refers to the use of a suspension as a feedstock in thermal spraying processes including plasma spraying (such as atmospheric plasma spraying and low pressure plasma spraying), high velocity oxygen fuel spraying, high velocity air fuel spraying, flame spraying, cold spraying, laser spraying or laser cladding. Preferably, the suspension according to the present invention is used in suspension plasma spraying and low pressure plasma spraying and high velocity oxygen fuel spraying, most preferably in suspension plasma spraying, specifically atmospheric suspension plasma spraying.

[0024] For purposes of this specification and claims, the Fine Fraction Ratio (FFR) is defined by Equation (1):

number

[0025] According to the invention, the fine fraction ratio is less than or equal to 0.5. Preferably, the fine fraction ratio is less than or equal to 0.4.

[0026] The FFR proposed in this specification has a density preferably between 3.0 and 7.0 g / cm 3 , more preferably 4.9 to 6.6 g / cm 3 Preferably, the ceramic particles are solid ceramic particles.

[0027] As used herein, the term "volume fraction" refers to the ratio of the total volume of solid ceramic particles having a particle size of 1.0 μm or less to the total volume of all solid ceramic particles in the suspension. Volume fraction is given in volume %.

[0028] Terms such as "mass fraction of solid ceramic particles in suspension" relate to the ratio of the total mass of all ceramic particles in suspension to the total mass of the suspension (i.e. the sum of the masses of all suspension components). Mass fractions are given in weight percent.

[0029] The volume fraction of particles having a size of 1.0 μm or less is determined from the particle size distribution obtained by particle size analysis. In the present invention, the particle size distribution is determined using laser diffraction particle analysis, preferably a "Microtrac" particle analyzer.

[0030] In such particle analyzers, a laser beam is scattered by the particles of the sample, with the light scattering angle being inversely proportional to the particle size. Particle size distributions are typically determined in intervals ("boxes").

[0031] According to the invention, in order to obtain a dense coating, it is particularly preferred to minimize the volume fraction of particles with a particle size of 1 μm or less. To determine the volume fraction of these particles from the particle size distribution, particle analyzer measurements are taken as close as possible to 1.0 μm. The value at 1.0 μm is then determined by linear interpolation if the instrument does not provide data for an interval exactly delimited by 1.0 μm.

[0032] In the present invention, the particle size distribution is determined using a Microtrac S3500 or Microtrac X100 instrument utilizing the Fraunhofer analysis mode (measurement mode: full range analysis (FRA) of light absorbing particles). Terms such as "full range analysis" refer to the determination of particle size over the entire measurement range of the instrument, and terms such as "light absorbing particles" refer to particles that do not transmit light.

[0033] The Microtrac S3500 and X100 instruments determine particle volume fraction in the interval ranging from 0.972 μm to 1.06 μm with 1.0 μm as the nearest value.

[0034] Other instruments exhibiting comparable sensitivity and measurement range to the Microtrac S3500 and X100 instruments, particularly comparable lower limits of detectable particle size and comparable sensitivity in the small size range, may be utilized to determine the particle size distribution according to the present invention. Those skilled in the art are aware of suitable instruments available on the market.

[0035] In a preferred embodiment, the volume fraction of solid ceramic particles having a size of 1.0 μm or less is 20% or more. The present invention is essentially beneficial for suspensions having a certain amount of small size particles. Thus, the present invention provides a teaching on the maximum amount of small size particles that should be contained in the suspension, if any small size particles are present at all.

[0036] According to a further preferred embodiment, the volume fraction of solid ceramic particles having a particle size of 1.0 μm or less is less than 30% by volume, preferably less than 25% by volume.

[0037] In a preferred embodiment, the solid ceramic particles of the suspension of the invention exhibit a particle size distribution with a d50 value in the range of 4.0 μm to 5.0 μm. The d50 value should be understood as the "average particle size" and is determined from the particle size distribution. The d50 value is known as the median size, i.e. the middle value of the particle size distribution, and is determined from a volumetric expression (dv50) or a number-based expression (dn50). In the present application, the d50 value refers to the volumetric expression, i.e. the particle size at 50% by volume in the cumulative distribution (for example, a d50 of 2.0 μm means that 50% by volume of the particles have a diameter smaller than 2.0 μm).

[0038] In one embodiment, the solid ceramic particles comprise or consist of at least one oxide of a transition metal, a rare earth metal, or a metal from Group 13 or 14 of the periodic table.

[0039] As used herein, the term "transition metal" refers to a transition metal element or mixtures thereof, i.e., two or more transition metal elements. According to IUPAC, a transition metal is an element whose atom has an incomplete d subshell or can give rise to a cation having an incomplete d subshell. However, for the purposes of this specification and claims, the term "transition metal" includes only elements of groups 4 to 11 of the periodic table and Zn.

[0040] As used herein, the term "rare earth metals" refers to a group of 17 chemically similar metallic elements including the lanthanides, yttrium and scandium. The lanthanides are defined as a set of elements with atomic numbers 57-71, all of which occur in nature except for promethium (Extractive Metallurgy of Rare Earths, CK Gupta, N. Krishnamurthy, CRC).

[0041] When the solid ceramic particles comprise or consist of an oxide of a transition metal, the oxide is preferably chromium(III) oxide (chromia, Cr 2 O 3) or titanium dioxide (titania, TiO x , x is preferably 1.6 to 2, even more preferably 1.6 to 1.9, or 2, i.e., TiO 2 ).

[0042] The solid ceramic particles may also be yttrium oxide (yttria, Y 2 O 3 ) may comprise or consist of an oxide of a rare earth metal.

[0043] When the solid ceramic particles comprise or consist of an oxide of a metal of group 13 of the periodic table, the oxide is preferably aluminum oxide (alumina, Al 2 O 3 ).

[0044] When the solid ceramic particles comprise or consist of a metal oxide of group 14 of the periodic table, the oxide is preferably silicon dioxide (silica, SiO 2 ), such as mullite, which is a type of silicate mineral that contains aluminum silicate (3Al 2 O 3 2SiO 2 ).

[0045] In a particularly preferred embodiment, the solid ceramic particles are chromium(III) oxide (Cr 2 O 3 ), aluminum oxide (Al 2 O 3 ), yttrium oxide (Y 2 O 3 ), titanium dioxide (TiO x where x is preferably in the range of 1.6 to 2), and mixtures and / or composites thereof.

[0046] According to a preferred embodiment, the mass fraction of the solid ceramic particles in the suspension is at least 60% by weight, preferably at least 70% by weight, even more preferably at least 75% by weight. The mass fraction of the solid ceramic particles in the suspension may also be at least 80% by weight or more.

[0047] According to the present invention, the solvent may comprise or consist of water or an organic solvent or a mixture thereof. The organic solvent may be selected from the group consisting of alcohols, ketones, esters, glycols, glycol ethers, glycol ether esters or hydrocarbons or any combination thereof.

[0048] Preferably, the solvent comprises or consists of water, preferably deionized water. The solvent may also comprise a cryoprotectant. The cryoprotectant is particularly useful when the solvent consists mainly or entirely of water. The solvent consists mainly of water when water constitutes at least 60% by weight of the solvent, preferably at least 70%, or 75%, or 80%, or 85%, or 90% by weight or more.

[0049] The cryoprotectant ensures that the suspension remains liquid and stable at temperatures below 0° C. This is beneficial for transportation and storage of the suspension. Preferably, the suspension remains liquid at least at −10° C. The cryoprotectant may be selected from the group of glycols and alcohols. Preferably, the cryoprotectant is ethylene glycol. The cryoprotectant may also be ethanol or isopropanol.

[0050] According to a particular embodiment of the invention, the solvent comprises a mixture of water and ethylene glycol. Preferably, the weight ratio of water to ethylene glycol ranges from 1:10 (w / w) to 1:1 (w / w). For example, the solvent may comprise 70% to 80% by weight of water and 30% to 20% by weight of ethylene glycol.

[0051] In one embodiment, the suspension according to the present invention further comprises a dispersant. The dispersant may be any compound suitable for stabilizing the suspension for thermal spraying. The dispersant ensures that the particles remain well dispersed and do not form large agglomerates or precipitates. For example, the dispersant may be a polymeric salt and an inorganic salt or an organic molecule. Those skilled in the art are aware of suitable dispersants for various solid ceramic particles.

[0052] Examples of suitable dispersing agents are 2-amino-2-methylpropanol (AMP 90™ and AMP 95™), ammonium polycarboxylate, 2-[2-(2-methoxyethoxy)ethoxy]acetic acid (MEEA), polyacrylic acid, polyethyleneimine, sodium metaphosphate, sodium tetraborate, triethanolamine, TRITON X-100™, Lopon® 888, sodium bicarbonate, and citric acid. 2 O 3 Particularly preferred dispersants are 2-amino-2-methyl-1-propanol and ammonium polycarboxylate. 2 O 3 A suitable dispersing agent for is 2-amino-2-methyl-1-propanol or 2-[2-(2-methoxyethoxy)ethoxy]acetic acid (MEEA).

[0053] However, the invention is not limited to this exemplary list of dispersants.

[0054] The concentration of the dispersant is selected to provide a homogeneous and stable suspension and reduce the viscosity depending on the concentration of solid ceramic particles in the suspension. The concentration of the dispersant may range from 0.1% to 10% by weight, preferably 0.5 to 5% by weight, even more preferably 1 to 3% by weight, for example 1% by weight, based on the content of solid ceramic particles.

[0055] The suspension according to the present invention may optionally further contain a binder.

[0056] Preferably, the viscosity of the suspension according to the present invention is between 100 and 1000 s -1 At a shear rate of 1000 s, the viscosity is less than 50 mPa*s, preferably less than 40 mPa*s, and even more preferably less than 30 mPa*s. The viscosity is usually measured at room temperature, which is in the range of 23 to 25°C. Preferably, the viscosity is less than 1000 s -1 More preferably, the viscosity is measured using an Anton Paar Physica MCR 301 rotational rheometer equipped with a plate-plate system.

[0057] A low viscosity is preferred for suspension spray processes.

[0058] The suspension according to the invention is particularly suitable for producing coatings with dense microstructure and smooth surface by suspension spraying, preferably suspension plasma spraying. As understood herein, "dense microstructure" is characterized by low porosity (i.e. less than 10%, preferably less than 5%) with small pores having a pore size of less than 20 μm, preferably less than 10 μm. In addition, dense coatings preferably do not have cracks of 50 μm or more, preferably 10 μm or more. Those skilled in the art are aware of suitable spraying parameters to obtain dense coatings.

[0059] These coatings are preferably used for corrosion, erosion and / or scuff protection of the coated material.

[0060] According to the present invention, dense coatings can be produced on any suitable substrate, such as metals, ceramics, polymers, ceramic matrix composites, alloys and mixtures or composites thereof, for example, the substrate may be made of aluminum, iron, steel, preferably stainless steel.

[0061] The suspensions described herein can be prepared by dispersing the solid ceramic raw materials in a solvent as described herein and milling the suspension until the desired average particle size (d50) is obtained. The milling is optionally carried out in the presence of a dispersant as described herein. The suspension is then diluted to the desired solids concentration.

[0062] The present invention will now be described in more detail in the following examples and comparative examples, but is not limited thereto. EXAMPLES

[0063] Example 1 As a raw material for the suspension, commercially available Cr with an average particle size (d50) of 4.3 was used. 2 O 3 Powder (10.192 kg) was used. 2 O 3 The purity of was >99% by weight. The particle size of the powder was measured in a measurement chamber using a Microtrac S3500 with 5 drops of 5% by weight TSPP dispersant (sodium pyrophosphate tetrabasic). The following parameters were used: Analysis mode: Fraunhofer, Measurement mode: "FRA" (full range analysis), Particle penetration: Absorption mode, Refractive index of water 1.33, Flow rate 50% and Internal ultrasonic power 30 watts for 40 seconds.

[0064] The raw materials were dispersed in 2.548 kg of deionized water at a solids concentration of 80% by weight. To reduce the viscosity of the raw material suspension, 102 g of dispersant Lopon® 888 (BK Giulini GmbH, Germany) were added to allow an intensive dispersion process. This corresponds to an amount of 1% by weight relative to the oxide content. The mixture was stirred for 15 minutes. The oxide material was ground in a WAB Dyno-Mill Multilab high energy ball mill. The grinding was carried out to obtain a well-dispersed suspension without agglomerates. Grinding balls of 1 mm diameter were used. The Cr thus produced was 2 O 3 The suspension contained 79.54% solids and 0.79% Lopon® 888 dispersant by weight.

[0065] The suspension was stirred from start to finish of the preparation to avoid settling of the particles. The density of the suspension was 2.8 g / ccm and was measured using a graduated cylinder and a scale. The viscosity of the suspension was in the range of 23-24 mPas at a shear rate of 100 1 / s, measured with a rheometer MCR301 (Anton Paar, Austria). The final PSD (particle size distribution) was d10: 0.24 μm, d50: 3.99 μm, d90: 8.82 μm. The sample for particle size measurement was prepared by diluting 10 ml of the suspension with 10 ml of deionized water and mixing it manually for 1 min with 5 drops of 5 wt.% TSPP dispersant (sodium pyrophosphate tetrabasic). A few drops of the sample thus prepared were used for the measurement. The instrument used was a Microtrac S3500. Before the start of the measurement, 5 drops of 5 wt.% TSPP dispersant were further placed in the measurement chamber. The following parameters were used: Analysis mode: Fraunhofer, Measurement mode: "FRA" (Full Range Analysis), Particle Penetration: Absorption mode, Refractive index of water 1.33, Flow rate 70% and Internal Ultrasonic Power 35 Watts for 50 seconds. The volume fraction of particles less than 1.0 μm was 21.76 vol.%. The calculated FFR was 0.27.

[0066] This suspension was used as a feedstock in a suspension plasma spray process. A suspension feeder (NanoFeeder™, Northwest Mettech) was used at a feed rate of 30 ml / min to feed the suspension to a spray torch (Axial III™, Northwest Mettech). The spray torch was operated with an argon-nitrogen-hydrogen plasma gas composition at a flow rate of 220 standard liters per minute with a power setting of 23-25 ​​kJ / l. The coating was deposited onto a grit-blasted stainless steel coupon of 25 mm diameter and 5 mm thickness with a spray distance of 140 mm (from the torch nozzle exit to the substrate surface). The sample was mounted on a fixture that rotated around a vertical axis at 106 revolutions / min. The spray torch was moved 14 times in a straight vertical direction over the rotating substrate to reach the desired coating thickness. Two air jets with 5 bar compressed air were mounted parallel to the torch and one air jet with 5 bar compressed air was mounted facing the coating sample to keep the coating surface at a temperature below 250° C. during coating deposition.

[0067] As shown in the SEM BSE images (Figures 1A and 1B), a coating with a dense, crack-free cross section and a smooth surface was obtained. The SEM BSE images were taken on the polished cross section of the coating. The coating cross section was mounted in epoxy resin, then smoothed with silicon carbide abrasive paper and polished with diamond suspension until the surface finish was completed with a mirror polish.

[0068] Example 2 As a raw material for the suspension, commercially available Cr with an average particle size (d50) of 4.3 μm was used. 2 O 3 Powder (20.0 kg) was used. Measurements were the same as those described in Example 1. Cr 2 O 3 The purity was greater than 99% by weight.

[0069] The raw materials were dispersed in 5.236 kg of a water / monoethylene glycol mixture at a solids concentration of 79.3 wt.%. The mixture was made by mixing 4.0 kg (76.4 wt.%) of deionized water and 1.236 kg (23.6 wt.%) of ethylene glycol (99%, Donau Chem GmbH, Austria). To reduce the viscosity of the raw material suspension, 200 g of dispersant Lopon® 888 (BK Giulini GmbH, Germany) was added to allow an intensive dispersion process. This corresponds to an amount of 1 wt.% relative to the oxide content. The oxide material was wet-milled in a WAB Dyno-Mill Multilab high-energy ball mill. The milling was carried out to obtain a well-dispersed suspension without agglomerates. Milling balls with a diameter of 1 mm were used. After milling, the suspension was pumped through a 40 μm sieve to remove coarse impurities. 300 ml of a water / MEG mixture was pumped through the mill to prevent bulk losses of the suspension. The liquids were combined and mixed with the suspension.

[0070] Cr produced in this way 2 O 3 The suspension contained a solids concentration of 78.7 wt.% and 0.79 wt.% of dispersant Lopon® 888. The suspension was stirred from start to finish to avoid particle settling. The final PSD was d10; 0.23 μm, d50: 3.66 μm, d90: 7.93 μm. The measurements were the same as those described in Example 1. The volume fraction of particles less than 1.0 μm was 24.25 vol.%. The calculated FFR was 0.31.

[0071] This suspension was used as a feedstock in a suspension plasma spray process. A suspension feeder (NanoFeeder™, Northwest Mettech) was used at a feed rate of 30 ml / min to feed the suspension to a spray torch (Axial III™, Northwest Mettech). The spray torch was operated with an argon-nitrogen-hydrogen plasma gas composition at a flow rate of 220 standard liters per minute with a power setting of 23-25 ​​kJ / l. The coating was deposited on a grit-blasted 50 x 30 x 5 mm stainless steel plate with a spray distance of 160 mm (from the torch nozzle exit to the substrate surface). The sample was mounted on a fixture that rotated about a vertical axis at 106 revolutions per minute. The spray torch was moved 96 times in a linear vertical direction over the rotating substrate to reach the desired coating thickness. Two air jets with 5 bar compressed air were mounted parallel to the torch and one air jet with 5 bar compressed air was mounted facing the coating sample to keep the coating surface at a temperature below 250° C. during coating deposition.

[0072] Coatings were obtained with dense, crack- and defect-free cross sections and smooth surfaces, as shown in the SEM BSE images of polished cross sections prepared in the same manner as described in Example 1 (FIG. 2).

[0073] Example 3 As a raw material for the suspension, commercially available Y 2 O 3 Powder (4.56 kg) was used. The measurements were the same as those described in Example 1. 2 O 3 The purity was greater than 99% by weight.

[0074] The suspension is subjected to the following steps: 1. The ingredients were dispersed in 1.97 kg of monoethylene glycol / MEG by slowly adding the powder while stirring the MEG. After stirring for 2.30 minutes, 1.03 kg of 1-hexanol was added to the mixture and stirred for an additional 30 minutes. 3. An additional 69 g of dispersant MEEA (2-(2-Methoxyethoxy)ethoxyacetic acid) (Amri Global) was added to reduce the viscosity of the suspension to less than 50 mPas at a shear rate of 100*1 / s. The suspension was stirred for an additional 30 minutes.

[0075] The Y produced in this way 2 O 3 The suspension contained 60.4 wt% solids and 0.90 wt% dispersant MEEA. The density of the suspension was 1.9 g / ccm, measured using a graduated cylinder and scale. The viscosity of the suspension ranged from 34 to 38 mPas at a shear rate of 100 1 / s, measured with a rheometer MCR301 (Anton Paar, Austria). The final PSD (particle size distribution) was d10: 0.52 μm, d50: 2.35 μm, d90: 5.64 μm. The measurements were the same as those described in Example 1. The volume fraction of particles less than 1.0 μm was 25.05 vol%. The calculated FFR was 0.41.

[0076] This suspension was used as a feedstock in a suspension plasma spray process. A suspension feeder (NanoFeeder™, Northwest Mettech) was used at a feed rate of 30 ml / min to feed the suspension to a spray torch (Axial III™, Northwest Mettech). The spray torch was operated with an argon-nitrogen-hydrogen plasma gas composition at a flow rate of 220 standard liters per minute with a power setting of 14.2 kJ / l. The coating was deposited on a grit-blasted alumina coupon of size 30×50 mm and thickness 4 mm with a spray distance of 115 mm (from the torch nozzle exit to the substrate surface). The sample was mounted on a fixture that rotated around a vertical axis at 318 revolutions per minute. The spray torch was moved 160 times in a linear vertical direction over the rotating substrate to reach the desired coating thickness. Two air jets with 4.1 bar compressed air were mounted parallel to the torch and one air jet with 4.1 bar compressed air was mounted facing the coating sample to keep the coating surface at a temperature below 250° C. during coating deposition.

[0077] As shown in the SEM BSE image of a polished cross section prepared in the same manner as described in Example 1 (FIG. 3), a coating with a dense, crack-free and defect-free cross section and a smooth surface was obtained.

[0078] Comparative Example 1 As a raw material for the suspension, commercially available Cr with an average particle size (d50) of 1.08 μm was used. 2 O 3 Powder (2.3 kg) was used. The particle size of the powder was measured in a measurement chamber using a Microtrac X100 with 5 drops of 5 wt% TSPP dispersant (sodium pyrophosphate tetrabasic). The following parameters were used: refractive index of water 1.33, flow rate 70% and internal ultrasonic power 35 watts for 50 seconds.

[0079] Cr 2 O 3 The purity was greater than 99% by weight.

[0080] The raw material was dispersed in a water / monoethylene glycol mixture at a solids concentration of 43.7 wt.%. The mixture was made by mixing 1.978 kg (66.7 wt.%) of deionized water and 0.989 kg (33.3 wt.%) of ethylene glycol (99%, Donau Chem GmbH, Austria). To reduce the viscosity of the raw material suspension, 23 g of dispersant AMP 90™ (BK Giulini GmbH, Germany) were added to allow a vigorous dispersion process. AMP 90™ contains 2-amino-2-methylpropanol and 10 wt.% water. The dispersant was added in an amount of 1 wt.% relative to the oxide content and stirred for 20 min using a dissolver disc. 4.6 kg of Cr with a measured solids concentration of 43.5 wt.% was thus produced. 2 O 3The suspension was used for the dilution step. 0.4 kg of deionized water was added during stirring to obtain a 40% by weight suspension. The suspension was stirred from start to finish to avoid settling of the particles. The solids concentration of the suspension thus produced was 40.05% by weight and the concentration of the dispersant AMP 90™ was 0.4% by weight.

[0081] The viscosity of the suspension was measured with a rheometer MCR301 (Anton Paar, Austria) in the range of 3-4 mPas at a shear rate of 100 1 / s. Final PSD (particle size distribution) measurements were performed using a Microtrac S3500 and the parameters of Example 1. The final PSD (particle size distribution) was d10: 0.16 μm, d50: 0.86 μm, d90: 2.54 μm. The volume fraction of particles less than 1.0 μm was 52.4 vol.%. The calculated FFR was 1.31.

[0082] Comparative Example 1A This suspension was used as a feedstock in a suspension plasma spray process. A suspension feeder (NanoFeeder™, Northwest Mettech) was used at a feed rate of 30 ml / min to feed the suspension to a spray torch (Axial III™, Northwest Mettech). The spray torch was operated with an argon-nitrogen-hydrogen plasma gas composition at a flow rate of 220 standard liters per minute with a power setting of 23-25 ​​kJ / l. The coating was deposited on a grid blasted steel tube with a diameter of 108 mm and a wall thickness of 4 mm at a spray distance of 160 mm (from the torch nozzle exit to the substrate surface). The tube was rotated about its horizontal axis at 382 revolutions / min. The spray torch was moved 30 times in a straight horizontal direction over the rotating tube to reach the desired coating thickness. Two air jets with 5 bar compressed air were mounted parallel to the torch and one air jet with 5 bar compressed air was mounted towards the tube surface to keep the coating surface at a temperature below 250° C. during coating deposition.

[0083] SEM analysis of polished cross-sections of the resulting coatings, prepared in the same manner as described in Example 1, revealed a bimodal coating structure with an uneven (rough) surface (Figures 4A-D).

[0084] Comparative example 1B The same suspension was used as a feedstock in a suspension plasma spray process. A suspension feeder (NanoFeeder™, Northwest Mettech) was used at a feed rate of 45 ml / min to feed the suspension to a spray torch (Axial III™, Northwest Mettech). The spray torch was operated with an argon-nitrogen-hydrogen plasma gas composition at a flow rate of 220 standard liters per minute with a power setting of 23-25 ​​kJ / l. The coating was deposited on a grit-blasted stainless steel coupon of 25 mm diameter and 5 mm thickness with a spray distance of 120 mm (from the torch nozzle exit to the substrate surface). The sample was mounted on a fixture that rotated around a vertical axis at 106 revolutions / min. The spray torch was moved 60 times in a linear vertical direction over the rotating substrate to reach the desired coating thickness. Two air jets with 5 bar compressed air were mounted parallel to the torch and one air jet with 5 bar compressed air was mounted facing the coating sample to keep the coating surface at a temperature below 300° C. during coating deposition.

[0085] SEM analysis of a polished cross-section of the resulting coating prepared in the same manner as described in Example 1 shows a generally flat surface with isolated / scattered surface irregularities in the form of bumps formed in a single column (Figure 5).

[0086] Comparative Example 2 As a raw material for the suspension, commercially available Cr with an average particle size (d50) of 4.3 μm was used. 2 O 3 Powder (5.0 kg) was used. Measurements were the same as those described in Example 1. Cr 2 O 3 The purity was greater than 99% by weight.

[0087] The raw materials were dispersed in 1.25 kg of a water / monoethylene glycol mixture at a solid concentration of 80 wt. %. The mixture was made by mixing 0.955 kg (76.4 wt. %) of deionized water and 0.295 kg (23.6 wt. %) of monoethylene glycol (99%, Donau Chem GmbH, Austria). To reduce the viscosity of the raw material suspension, 50 g of dispersant Lopon® 888 (BK Giulini GmbH, Germany) was added to allow the grinding process. The dispersant was added in an amount of 1 wt. % with respect to the oxide content. The oxide material was wet-ground in a WAB Dyno-Mill Multilab high-energy ball mill. The grinding was carried out to obtain a well-dispersed suspension without agglomerates. YSZ grinding balls were used. After grinding, the suspension was pumped through a 40 μm sieve to remove coarse impurities. 500 ml of a water / MEG mixture was pumped through the mill to prevent bulk loss of the suspension. This liquid was combined and mixed with the suspension. Cr produced in this way 2 O 3 The suspension had a solids concentration of 78.25 wt.%. The suspension was stirred from start to finish to avoid settling of the particles. The density of the suspension was 2.6 g / ccm, measured using a graduated cylinder and scale. The solids concentration of the suspension was diluted to 40.05 wt.% by adding 6.2 kg of the above water / MEG mixture. The viscosity of the suspension was in the range of 2-3 mPas at a shear rate of 100 1 / s, measured with a rheometer MCR301 (Anton Paar, Austria). The final PSD (particle size distribution) was d10: 0.22 μm, d50: 3.90 μm, d90: 8.81 μm. The measurements were the same as those described in Example 1. The volume fraction of particles less than 1.0 μm was 23.63 vol.%. The calculated FFR was 0.59.

[0088] This suspension was used as a feedstock in a suspension plasma spray process. A suspension feeder (NanoFeeder™, Northwest Mettech) was used at a feed rate of 45 ml / min to feed the suspension to a spray torch (Axial III™, Northwest Mettech). The spray torch was operated with an argon-nitrogen-hydrogen plasma gas composition at a flow rate of 220 standard liters per minute with a power setting of 23-25 ​​kJ / l. The coating was deposited onto a grit-blasted stainless steel coupon of 25 mm diameter and 5 mm thickness with a spray distance of 120 mm (from the torch nozzle exit to the substrate surface). The sample was mounted on a fixture that rotated around a vertical axis at 106 revolutions / min. The spray torch was moved 40 times in a linear vertical direction over the rotating substrate to reach the desired coating thickness. Two air jets with 5 bar compressed air were mounted parallel to the torch and one air jet with 5 bar compressed air was mounted facing the coating sample to keep the coating surface at a temperature below 300° C. during coating deposition.

[0089] It was not possible to obtain satisfactory SEM BSE images of the coating cross-section.

Claims

1. A suspension for suspension thermal spraying, comprising solid ceramic particles and a solvent, characterized in that the suspension has a fine fraction ratio of 0.5 or less, said fine fraction ratio being: - the volume fraction of solid ceramic particles having a size of 1.0 μm or less as determined from a particle size distribution obtained from particle size analysis using laser diffraction particle analysis; - the mass fraction of solid ceramic particles in the suspension; It is defined as the ratio of The density of the solid ceramic particles is 3.0 to 7.0 g / cm 3 and The solid ceramic particles are d 50 The suspension has a particle size distribution with a value ranging from 2 μm to 10 μm.

2. 2. The suspension of claim 1, wherein the volume fraction of the solid ceramic particles having a particle size of 1.0 μm or less is 20% or more.

3. The density of the solid ceramic particles is 4.9 to 6.6 g / cm 3 3. The suspension according to claim 1 or 2,

4. The solid ceramic particles are 2 O 3 , Al 2 O 3 , Y 2 O 3 , TiO x 3. The suspension according to claim 1 or 2, selected from the group consisting of: wherein x is preferably in the range of 1.6 to 2, and mixtures and / or composites thereof.

5. 3. The suspension according to claim 1 or 2, wherein the volume fraction of the solid ceramic particles having a particle size of 1.0 μm or less is less than 30 vol.%, preferably less than 25 vol.%.

6. The solid ceramic particles have a diameter of d in the range of 4 μm to 5 μm. 50 3. The suspension according to claim 1 or 2, having a particle size distribution comprising a value.

7. 3. The suspension according to claim 1 or 2, wherein the solvent comprises or consists of water.

8. 3. The suspension according to claim 1 or 2, wherein the solvent comprises a cryoprotectant.

9. 9. The suspension according to claim 8, wherein the antifreeze agent comprises or consists of a glycol (preferably ethylene glycol) or an alcohol (preferably ethanol or isopropanol).

10. 3. The suspension according to claim 1 or 2, wherein the solvent consists of a mixture of water and ethylene glycol, the weight ratio of water to ethylene glycol being in the range of 1:10 (w / w) to 1:1 (w / w).

11. 3. A suspension according to claim 1 or 2, further comprising a dispersing agent.

12. 3. Suspension according to claim 1 or 2, wherein the mass fraction of the solid ceramic particles in the suspension is at least 60% by weight, at least 70% by weight, preferably at least 75% by weight.

13. 3. Suspension according to claim 1 or 2, wherein the fine fraction ratio is less than or equal to 0.4, preferably less than or equal to 0.

35.

14. 3. A suspension according to claim 1 or 2, wherein the viscosity of the suspension, measured as described herein, is less than 50 mPa*s, preferably less than 40 mPa*s, even more preferably less than 30 mPa*s.

15. 3. Use of the suspension according to claim 1 or 2 for suspension spraying, preferably suspension plasma spraying.

16. 16. The use according to claim 15 for producing a coating on a substrate, wherein said substrate is selected from the group consisting of metals, ceramics, polymers, alloys and mixtures thereof.